2006
DOI: 10.1057/palgrave.jibs.8400193
|View full text |Cite
|
Sign up to set email alerts
|

MNEs and industrial structure in host countries: a portfolio analysis of Irish manufacturing

Abstract: Ireland has been very successful in attracting foreign MNEs in high-technology sectors. Although these sectors exhibit faster growth than the traditional low-technology sectors populated primarily by indigenous firms, the high-technology sectors are also more volatile. We use portfolio theory to show that Ireland's FDI strategy has led to a more diversified manufacturing sector that exhibits higher growth without a commensurate increase in volatility and risk. Journal of International Business Studies (2006) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…the case of ireland demonstrates how a small country can attract FDi because of its stock of desirable resources and its ability to develop this stock (Barry/Kearney 2006). this study found that FDi had also contributed to diversifying the industrial structure of ireland, especially in high technology sectors, and had help to make industry growth paths more stable.…”
Section: Fdi Inflows Into Small Developed Countriesmentioning
confidence: 66%
“…the case of ireland demonstrates how a small country can attract FDi because of its stock of desirable resources and its ability to develop this stock (Barry/Kearney 2006). this study found that FDi had also contributed to diversifying the industrial structure of ireland, especially in high technology sectors, and had help to make industry growth paths more stable.…”
Section: Fdi Inflows Into Small Developed Countriesmentioning
confidence: 66%
“…Contrastingly, studies highlighting the degree to which firms are strengthening their value chain linkages in order to achieve operational efficiency are numerous (Barry & Kearney, 2006;Farrell, 2006;Hill, Marino & Chae, 2003;Kim, Cavusgil & Calantone, 2006;Kuei, Madu, Chow & Lu, 2005;Liker & Morgan, 2006). This difference in available research may be attributed, in part, to the well-documented benefits attributed to value chain improvements assessed by many academics and business practitioners.…”
Section: The Weak Bonds Between Ict Km and Creativitymentioning
confidence: 99%
“…1 The spillover effect can enhance the competitive advantage of domestic firms and can be facilitated by horizontal and vertical linkages between domestic and foreign firms. The importance of FDI-generated spillovers has been highlighted by, among others, Javorcik (2004), Keller (2004), Scott-Kennel and Enderwick (2005), Barry and Kearney (2006), Wei and Liu (2006), Scott-Kennel (2007), De Beule and Bulcke (2009), and Meyer and Sinani (2009).…”
Section: Introductionmentioning
confidence: 99%